Efektivitas Bimbingan Kelompok dengan Teknik Diskusi untuk Meningkatkan Konsep Diri Positif Siswa - Khasanah, Tia Nur; Kurniawan, Drajat Edy (Indonesian Journal of Educational Counseling, 2023)
This study aims to test the effectiveness of group guidance with discussion techniques in increasing the positive self-concept of class X Dance students of SMK Negeri 1 Kasihan. The type of research used is a pre-experimental design with a one-group pretest-posttest design. The population in this study were all class X Dance students at SMK Negeri 1 Kasihan. The sample in this study was 6 students who were taken using a purposive sampling technique. The data collection method in this study uses a questionnaire. The data analysis technique of this study used a paired sample test. Based on the results of the paired samples test, a t value of -8.794 was obtained with a signifikansi value of 0,000 < 0,05 so that it can be said that there is a significant difference between the average pretest and posttest scores of student's self-concept. Judging from the mean, the posttest score was higher than the pretest score, namely 129,00 > 91,50, which means there was an increase in students' positive self-concept. Based on these results it can be concluded that group guidance using discussion techniques is effective for increasing the positive self-concept of class X Dance students at SMK Negeri 1 Kasihan.